The biomechanical changes of facet joint violation after transforaminal lumbar interbody fusion combined with decompression surgery: a finite element study - Chen, Xing; Zhao, Geng; Wang, Xiaoxiong; Zhang, Yuchen; Sun, Junyuan; Zhang, Xu; Liu, Xinyu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionFacet joint violation (FJV) is a common complication of intervertebral fusion surgery, altering the load-bearing capability of the facet joints and ultimately contributing to segmental instability. Furthermore, adjacent segment degeneration is one of the potential long-term complications following lumbar spinal intervertebral fusion. For patients with a history of lumbar intervertebral fusion who developed symptomatic spinal stenosis at adjacent segments, adjacent segment decompression surgery is a clinically viable option. The biomechanical effects of isolated decompression surgery or intervertebral fusion surgery have been relatively well established. However, the biomechanical impact of facet joint intrusion on patients who have undergone both lumbar intervertebral fusion and adjacent segment decompression remains unclear.MethodsThe L4-L5 intervertebral fusion model (F) and the L3-L4 decompression with L4-L5 intervertebral fusion model (DF) were developed based on a validated intact L3-L5 model (I). On the basis of DF model, six FJV models were created according to the extent and grades of facet joint violation: left mild violation (LMV), left severe violation (LSV), right mild violation (RMV), right severe violation (RSV), bilateral mild violation (BMV), and bilateral severe violation (BSV). In each scenario, the range of motion (ROM) and intradiscal pressure (IDP) at the supra-adjacent segments were analyzed.ResultsThe results indicated that both decompression and intervertebral fusion surgeries increased the ROM and intradiscal stress on the L3-L4 intervertebral discs. Additionally, the presence of facet joint violation further increased the ROM and intradiscal pressure on the L3-L4 segment, with these changes being associated with the grades and extent of facet joint violation, particularly when decompression and violation occurred on the same side.DiscussionThis study revealed that decompression or facet joint violation could elevate intradiscal pressure and ROM at the supra-adjacent segment, indicating a potential synergistic interaction between these two risk factors.